Answer:
u= 2.5
Step-by-step explanation:
Using BIDMAS
Step 1: Expand the bracket
9(u-2) + 1.5u=8.25
9u-18+1.5u=8.25
Step 2: collect like terms
9u+1.5u=8.25+18
10.5u=26.25
Step 3: Divide both sides by 10.5 to get u
u=
= 2.5
Answer:
y=-x+3.
Step-by-step explanation:
The graph goes down one and right one before making another point. This means that the slope is -1/1. Simplify and you get -1. So far we have y=-1x. -1x is the same as -1. Now we have y=-x. The graph intersects the y-axis at the point (0,3). This makes our y-intercept 3. Our final equation is y=-x+3.
<h3>
Answer:</h3><h3>All of them meet at the gym again after 48 days and it will be tuesday</h3>
Step-by-step explanation:
Lily goes to gym once every 8 days.
Such that she will visit on 8, 16 , 24, 32 , 40, 48th days
Ann goes once every 12 days
Such that she will visit on 12, 24, 36, 48, 60th days ....
Taylor comes once every 16 days
Such that she will visit on 16, 32, 48, 64th days....
Comparing the common days on which they will visit again after wednesday,
it will be after 48 days, (i.e) after 6 weeks and 5 days, it will be tuesday
264 yards...
While multiplying decimals by 10, 100, 1,000 and so on, just move the decimal to the right by how many zeros you have in the number. Let’s say I have 7.9 x 10. Move the decimal one place to the right because you have ONE zero. Then your answer would be 79.
Solving a system of linear equations, we conclude that the measure of side Z is 2√13
<h3>How to find the measure of side Z?</h3>
Remember the Pythagorean theorem. It says that the square of the hypotenuse is equal to the sum of the squares of the legs.
In the image, we can identify 3 right triangles, and with the Pythagorean theorem, we can write a system of 3 equations.
x^2 = y^2 + 4^2
z^2 = y^2 + 9^2
(4 + 9)^2 = z^2 + x^2
We want to solve that for z.
Now, the second equation can be rewritten to:
y^2 = z^2 - 9^2
Now let's replace the first equation into the third one, so we get:
(4 + 9)^2 = z^2 + (y^2 + 4^2)
Now we can replace y^2 by z^2 - 9^2
(4 + 9)^2 = z^2 + ((z^2 - 9^2) + 4^2)
Now we can solve this:
(13)^2 = z^2 + z^2 - 9^2 + 4^2
(13)^2 + 9^2 - 4^2 = 2*z^2
104/2 = z^2
52 = z^2
√52 = z
√(4*13) = z
√4*√13 = z
2√13 = z
We conclude that the measure of side Z is 2√13
If you want to learn more about systems of equations:
brainly.com/question/13729904
#SPJ1